Analysis of Dental Arch in Children With Oral Cleft Before and After the Primary Surgeries. Issue 8 (November 2019) - Mello, Bianca Zeponi Fernandes; Ambrosio, Eloá Cristina Passucci; Jorge, Paula Karine; de Menezes, Márcio; Carrara, Cleide Felício Carvalho; Soares, Simone; Valarelli, Fabrício Pinelli; Moreira Machado, Maria Aparecida Andrade; Oliveira, Thais Marchini
Abstract : Abstract: This study aimed to evaluate longitudinally the alteration of the dental arch dimensions of children with different oral cleft types, before and after the primary surgeries. Three-dimensional images of the maxillary dental casts of children with unilateral complete cleft lip (G1), unilateral complete cleft lip and palate (G2), and cleft palate (G3). The children were evaluated at pre-cheiloplasty (T1), pre-palatoplasty (T2), and 1 year after palatoplasty (T3). The measurements obtained: intercanine (C-C') and intertuberosity (T-T') distances, anterior (I-CC') and total (I-TT') arch lengths. To analyze the intraexaminer error, paired t -test was applied and Dahlbergh formula. The intragroups comparisons were applied: paired t -test, ANOVA followed by Tukey, Wilcoxon test, and Kruskal–Wallis test followed by Dunn test. The intergroup comparisons were performed by independent t -test and Mann–Whitney test. In G1, the C-C', T-T', and the I-TT' distances revealed a significant increase of the maxilla. In G2, the C-C' distance statistically decreased from T1 to T3, T-T' distance showed statistical increase from T1 to T3. The I-TT' length increased with statistically significant differences between T1 and T3, T2 and T3. In G3, the C-C', T-T', and I-TT' distance increased was statistically significant. The longitudinal evaluation of the changes occurred in the dental arches with different oral cleft types showed that cheiloplasty and palatoplasty caused the most alterations in the development of the maxillary dimensions of children with complete cleft lip and palate. Abstract : Supplemental Digital Content is available in the text